Developing C# apps for iPhone and iPad using MonoTouch iOS apps development for .NET developers - Costanich, Bryan (Berkeley, California Apress, 2011)
Developing C# Applications for iPhone and iPad using MonoTouch shows you how to use your existing C# skills to write apps for the iPhone and iPad. Fortunately, there's MonoTouch, Novell's .NET library that allows C# developers to write C# code that executes in iOS. Furthermore, MonoTouch allows you to address all the unique functions of the iPhone, iPod Touch, and iPad. And the big plus: You needn't learn any Objective-C to master MonoTouch! Former Microsoft engineer and published app-store developer Bryan Costanich shows you how to use the tools you already know to create native apps in iOS using C# and the .NET Base Class Libraries. The magic is in Novell's implementation of Apple's Cocoa libraries in MonoTouch. You'll master the same elegant and rich Cocoa environment, but without the need to learn a new programming language. Developing C# Applications for iPhone and iPad using MonoTouch takes you from your first Hello, World example through the major APIs and features of iOS. The coverage is comprehensive and makes use of frequent examples, complete with sample code you can download and reuse to create your own powerful and playful apps.
Electronic reproduction.
Keywords: iPhone (Smartphone) -- Programming; iPad (Computer) -- Programming; Application software -- Development; C# (Computer program language).